THE PATRISTICS SCHOLASTICS AND ARABIANS THE MYSTICAL REACTION - ROSSI, GIOVANNI; BALDWIN, JAMES MARK (Departamento de Salud Publica, CD MEXICO, DF, MEX, 1913)
chapter- Discusses the psychological aspects of dualism as presented by the Patristics, Scholastics, Arabians, and Mystics (PsycINFO Database Record © 2008 APA, all rights reserved)
Keywords: PATRISTICS SCHOLASTICS, ARABIANS, MYSTICAL REACTION; FILOSOFIA; FILOSOFIA DEL CONOCIMIENTO